Moderating effects of perceived social support on self-efficacy and psychological well-being of Chinese nurses: a cross-sectional study - Lu, Jiachen; Wang, Bin; Dou, Xiaofeng; Yu, Yingying; Zhang, Yanni; Ji, Haoqiang; Chen, Xu; Sun, Meng; Duan, Yuxin; Pan, Yuanping; Chen, Yunting; Yi, Yaohui; et al. (Frontiers in Public Health, 2023)
Introduction Nurses experience significant physical and psychological stress that negatively influences their psychological well-being. The objective of this study was to explore the association between self-efficacy and psychological well-being among Chinese nurses and to assess the moderating effects of perceived social support (PSS). Methods In 2020, a hospital-based cross-sectional study using a multistage random sampling approach was performed in five regions of Liaoning, China. Of the 1,200 surveyed nurses, 1,010 completed questionnaires that evaluated the demographic information, 14-item Hospital Anxiety and Depression Scale, General Self-Efficacy Scale, and Multidimensional Scale of Perceived Social Support. To examine the factors associated with mental health parameters, hierarchical multiple regression analysis was performed. The interactions were visualized using a simple slope analysis. Results The mean depression and anxiety scores for Chinese nurses were 8.74 ± 3.50 and 6.18 ± 3.26, respectively. The association between self-efficacy and depression differed between the low perceived social support (PSS) group (1 SD below the mean, β = −0.169, p < 0.01) and high PSS group (1 SD above the mean, β = −0.077, p < 0.01). Similarly, the association between self-efficacy and anxiety differed between the low PSS group (1 SD below the mean, β = −0.155, p < 0.01) and high PSS group (1 SD above the mean, β = −0.044, p < 0.01). Conclusion We found that Chinese nurses experienced high levels of anxiety and depression. Furthermore, PSS moderates the relationship between self-efficacy and psychological well-being. Therefore, interventions targeting self-efficacy and PSS should be implemented to improve the psychological well-being of nurses.